A protocol for a systematic review of randomised evaluations of strategies to improve recruitment of rural participants to randomised controlled trials - Heidi Green; Charlotte Murray; Lucy Thompson; Naomi Young; Shaun Treweek; Philip Wilson (James Cook University, 2023)
Introduction: People living rurally face health inequities fuelled by social exclusion, access to and awareness of health services, and poor transport links. In order to improve the acceptability, accessibility and applicability of health and care interventions, it is important that clinical trial participant populations include people living rurally. Identifying strategies that improve recruitment of rural participants to trials will support trialists, reduce research waste and contribute to alleviating health inequalities experienced by rural patients. The objective of the review is to quantify the effects of randomised evaluations of strategies to recruit rural participants to randomised controlled trials. Methods: The following databases will be searched for relevant studies: Ovid MEDLINE, Embase, Cochrane Library, Web of Science All, EBSCO CINAHL, Proquest, ERIC, IngentaConnect, Web of Science SSCI and AHCI, and Scopus. Any randomised evaluation of a recruitment intervention aiming to improve recruitment of rural participants to a randomised trial will be included. We will not apply any restriction on publication date, language or journal. The primary, and only, outcome of our review will be the proportion of participants recruited to a randomised controlled trial. Two reviewers will independently screen abstracts and titles for eligible studies, and then full texts of relevant records will be reviewed by the same two reviewers. Where disagreements cannot be resolved through discussion, a third reviewer will adjudicate. Results: We will assess the methodological quality of individual studies using the Cochrane risk of bias tool, and the GRADE approach will be applied to determine the certainty of the evidence within each comparison. Conclusion: This systematic review will quantify the effects of randomised evaluations of strategies to recruit rural participants to trials. Our findings will contribute to the evidence base to support trial teams to recruit a participant population that represents society as a whole, informing future research and playing a part to alleviate health inequalities between rural and urban populations.